Factors (Antecedents) Influencing Creation and Fate of Innovations and their Organizations – III - Glor, Eleanor D (Innovation Journal, 2021)
Despite recommendations for more quantitative analyses of public sector innovation factors (Glor, 2014a; de Vries, Bekker and Tummers, 2016), there has been limited examination of them. This paper identifies and explores six factors (ideology, politics, the economy, external support, resources, effects) that influenced the introduction and survival or termination of the first time these public sector innovations and their five organizations (I&O) were introduced in North America. It assesses their key antecedent factors before creation (Time 1) and the same factors again at the time of their fate 15 to 44 years later (Time 2). They were assessed with a new measurement instrument examining the six factors (Glor, 2017a). The tool has 1267 statements (items) and 555 pairs of data, with scoring distributed on a five-point Likert scale. Three expert raters completed the instrument (Glor, 2017b). Based on mean scores, the most important factors in Time 1 (creation of I&O) were found to be the economy, resources, effects and external support and in Time 2 (survival/termination) ideology and politics. This methodology could potentially be used to study the remaining 154 Government of Saskatchewan (GoS) population’s innovations and that of other populations.

Analysis of Antecedents of Trailblazing and Adoption of Public Policy Innovation Identified by a Systematic Literature Review - II - Glor, Eleanor D (2021)
The paper organizes and summarizes the conditions (antecedents) researchers and practitioners identified as occurring prior to trailblazing and adoption of public policy (including program) innovation, as identified in a systematic literature review. The review identified 87 relevant documents and 594 antecedents. Trailblazing of innovation is Rogers’ (1995) first two stages of adoption—innovation (invention) and early adoption (identified here as second and third adoptions in a government’s community or population). The antecedents are analyzed into grouped antecedents, factors and clusters. The most-mentioned grouped antecedents were citizen pressure, process, structure and political culture. The most-mentioned factors were innovation drivers, people, policy/process, and context. The factors were organized into clusters—external, political and internal. Based on number of mentions the literature considered the internal cluster the most important. The most-mentioned factors in external cluster were context and people; in political cluster, drivers, political context and political actors; in internal cluster, innovation process, drivers, people and internal environment. Multiples more antecedents were identified for internal cluster than the others. Lack of consistent definitions and the mixing of stages and levels in the literature has hampered understanding of antecedents and placed limitations on this study. The literature sometimes distinguished external and internal cluster; the current analysis also considers a political cluster, which is especially important to trailblazing of public policy innovations.

A Comparison of Antecedents of Different Types of Innovation – V - Glor, Eleanor D (Innovation Journal, 2021)
Antecedents of innovation precede their implementation and probably influence which innovations and whether they are approved and implemented. Antecedents have been identified in a considerable number of types of innovation. Are they the same in these types? A systematic literature review (SLR) of antecedents of policy innovation found 594 antecedents, 508 of them unique, in 87 articles on trailblazing and adoption. So many antecedents suggest a lack of clarity about what the antecedents of policy innovation may be. They have been clarified for policy innovation. In this paper the antecedents of policy innovation are compared to antecedents of private, public sector and social innovation identified in literature reviews, SLRs and metaanalyses to see whether common or different antecedents are identified in these literatures. While the literature often implies antecedents of different types of innovation are the same by lumping them together, they were found to vary somewhat by type of innovation, especially trailblazing and higher-level factors and clusters. External antecedents were only found to be important for policy innovation and dissemination; political antecedents were particularly important for trailblazing; internal antecedents were important for all types of innovation. Literature on antecedents of private innovations did not consider external or political antecedents. Four research questions are addressed: Q. 1: At what level should antecedents of innovation be analyzed and compared? Q. 2: How do antecedents identified for different types of innovation compare—private, public and public-social sectors? Q. 3: How do clusters identified for different types of public sector innovation compare— processes; trailblazing and adoption of policy; dissemination; private, public, public-social sectors? Q. 4: Do a common set of unique and grouped antecedents, factors and clusters influence all types of innovation equally or are their antecedents discernably different? Key words: antecedents of innovation, comparison of antecedents, types of innovation, systematic literature review.

Comparisons of Antecedents of Trailblazing/Adoption and Quantitative/Qualitative Studies of Public Policy Innovation Identified in a Systematic Literature Review – IV - Glor, Eleanor D (Innovation Journal, 2021)
Are the antecedents identified in trailblazing/adoption and quantitative/qualitative public policy innovation studies similar or different? This quantitative study answers this question by identifying, categorizing and analyzing their antecedents, identified in a systematic literature review (SLR). Trailblazing is the first three adoptions of an innovation in its population/ community, adoption is all adoptions, in any organization. If their antecedents were different, this would lend credibility to the idea that they are different phenomena. The criteria for inclusion in the SLR were met by 87 publications; 594 antecedents were identified. Analysis identified 508 unique antecedents, 28 grouped antecedents, 5 factors and 3 clusters.

Studying the Impact of Innovation on Organizations, Organizational Populations and Organizational Communities: A Framework for Research - Glor, Eleanor D (Innovation Journal, 2014)

Factors and Factor Clusters Most Influential in Introduction and Global Fate of Innovations and their Organizations – IV - Glor, Eleanor D (Innovation Journal, 2019)
Analysis of factors (antecedents) influencing the introduction and fate of innovations and their organizations (I&O) has been limited. Most of the innovation literature has focused on introduction and dissemination but not fate of I&O. It often found ideology and politics were not important in introduction of I&O. Glor (2017a, b) studied six factors influencing the introduction and survival/mortality of the first introduction in USA and Canada of ten public sector I&O introduced by the Government of Saskatchewan, (GoS), a Canadian provincial government, 1971 to the present. She reported assessment of their antecedent factors before introduction (Time 1) and those factors again at the time of survival/termination, 15 to 46 years later (Time 2). Introduction and survival/termination are defined by their appearance in/disappearance from Budget Estimates, annual reports and Public Accounts. I&O studied were the full sub-population of income security I&O introduced. A new, valid instrument was used to assess the influences, examining six factors and some clusters thought by three experts to have influenced their introduction and fate. The expert raters responded to 1267 statements (items), 555 pairs between times 1 and 2 distributed on five-point Likert scales. For all ten I&O, the factors ideology, politics, economy, external support, resources and effects were considered. In this paper, factors and clusters of factors are explored to attempt to predict survival or termination in Time 2, using means, analysis of variance (ANOVA), paired t-test and logistic regression analyses. Clusters were considered, such as external/internal clusters, external cluster and external support factor compared to economy factor and internal cluster. The best combination of factors and clusters for predicting introduction of I&O in Time 1 was found to be economy factor and internal cluster (resources, effects). The best combination for predicting fate (survival/ termination) in Time 2 was political cluster (ideology, politics) and external support factor. These results are important for practitioners, to point the way to successful introduction of I&O and for scholars, to understand important influences on fate. The dominance of resource factors in introduction was as expected and consistent with the literature. The capacity to predict either survival or termination had not been studied before: Political factors dominated survival and termination.

Can the PRISMA Protocol be used to Guide a Systematic Literature Review of Antecedents of Policy Innovation Trailblazing and Adoption? – I - Glor, Eleanor D (Innovation Journal, 2021)
Methodology for systematic literature reviews (SLRs) is not well developed in public policy compared to the health field. This paper explores use of the health PRISMA protocol for SLRs to guide an SLR of antecedents of trailblazing and adoption of public policy innovation and whether it is a suitable protocol for public policy. Trailblazing is the first two stages—invention and early adoption—of Rogers’ (1995) five stages of innovation adoption in a governmental or organizational population. Completing applicable items in the checklist, a SLR of 87 peerreviewed publications identified 594 antecedents; trailblazing/adoption and empirical/nonempirical studies are distinguished and the theories reflected are identified.

Conclusion: Important Antecedents of Public Policy Innovation as Revealed in a Systematic Literature Review – VI - Glor, Eleanor D (Innovation Journal, 2021)
A systematic literature review (SLR) of antecedents of trailblazing and adoption of public policy innovation was conducted. Many antecedents were found—594. A terminology and classification system for them was therefore developed (unique antecedents-508, grouped antecedents-28, factors-15, clusters-3). Differences among trailblazing/adoption and quantitative/qualitative studies were explored six ways. Eleven grouped antecedents of trailblazing were importantly different from those of adoption, 17 were not. Grouped antecedents of quantitative and qualitative studies were not importantly different and so were used as the standard. Only trailblazing had different antecedents from the other three types of study (adoption, quantitative, qualitative). Eight grouped antecedents were the best indicators of policy innovation. Of the three clusters of antecedents, external and internal cluster grouped antecedents were equally important for all four kinds of study; political cluster antecedents were different for trailblazing. Although there was no one best political indicator (large difference from adoption) for trailblazing, political cluster was more important for trailblazing than adoption. Political cluster was higher (had a higher proportion of mentions) and internal cluster lower for trailblazing; political cluster was lower and internal cluster higher for adoption. The important antecedents for public policy innovation were compared to those for the private/public sector, public process/policy and public/social innovation: Differences were found. The best antecedent indicators of trailblazing of policy innovation identified in the literature were external environment, drivers, obstacles (external) and people (internal).

Factors and Factor Clusters Most Influential in Introduction and Global Fate of Innovations and their Organizations – IV - Glor, Eleanor D (Innovation Journal, 2019)
Analysis of factors (antecedents) influencing the introduction and fate of innovations and their organizations (I&O) has been limited. Most of the innovation literature has focused on introduction and dissemination but not fate of I&O. It often found ideology and politics were not important in introduction of I&O. Glor (2017a, b) studied six factors influencing the introduction and survival/mortality of the first introduction in USA and Canada of ten public sector I&O introduced by the Government of Saskatchewan, (GoS), a Canadian provincial government, 1971 to the present. She reported assessment of their antecedent factors before introduction (Time 1) and those factors again at the time of survival/termination, 15 to 46 years later (Time 2). Introduction and survival/termination are defined by their appearance in/disappearance from Budget Estimates, annual reports and Public Accounts. I&O studied were the full sub-population of income security I&O introduced. A new, valid instrument was used to assess the influences, examining six factors and some clusters thought by three experts to have influenced their introduction and fate. The expert raters responded to 1267 statements (items), 555 pairs between times 1 and 2 distributed on five-point Likert scales. For all ten I&O, the factors ideology, politics, economy, external support, resources and effects were considered. In this paper, factors and clusters of factors are explored to attempt to predict survival or termination in Time 2, using means, analysis of variance (ANOVA), paired t-test and logistic regression analyses. Clusters were considered, such as external/internal clusters, external cluster and external support factor compared to economy factor and internal cluster. The best combination of factors and clusters for predicting introduction of I&O in Time 1 was found to be economy factor and internal cluster (resources, effects). The best combination for predicting fate (survival/ termination) in Time 2 was political cluster (ideology, politics) and external support factor. These results are important for practitioners, to point the way to successful introduction of I&O and for scholars, to understand important influences on fate. The dominance of resource factors in introduction was as expected and consistent with the literature. The capacity to predict either survival or termination had not been studied before: Political factors dominated survival and termination.

Can the PRISMA Protocol be used to Guide a Systematic Literature Review of Antecedents of Policy Innovation Trailblazing and Adoption? – I - Glor, Eleanor D (Innovation Journal, 2021)
Methodology for systematic literature reviews (SLRs) is not well developed in public policy compared to the health field. This paper explores use of the health PRISMA protocol for SLRs to guide an SLR of antecedents of trailblazing and adoption of public policy innovation and whether it is a suitable protocol for public policy. Trailblazing is the first two stages—invention and early adoption—of Rogers’ (1995) five stages of innovation adoption in a governmental or organizational population. Completing applicable items in the checklist, a SLR of 87 peerreviewed publications identified 594 antecedents; trailblazing/adoption and empirical/nonempirical studies are distinguished and the theories reflected are identified.

Studying the Impact of Innovation on Organizations, Organizational Populations and Organizational Communities: A Framework for Research - Glor, Eleanor D (Innovation Journal, 2014)

Comparisons of Antecedents of Trailblazing/Adoption and Quantitative/Qualitative Studies of Public Policy Innovation Identified in a Systematic Literature Review – IV - Glor, Eleanor D (Innovation Journal, 2021)
Are the antecedents identified in trailblazing/adoption and quantitative/qualitative public policy innovation studies similar or different? This quantitative study answers this question by identifying, categorizing and analyzing their antecedents, identified in a systematic literature review (SLR). Trailblazing is the first three adoptions of an innovation in its population/ community, adoption is all adoptions, in any organization. If their antecedents were different, this would lend credibility to the idea that they are different phenomena. The criteria for inclusion in the SLR were met by 87 publications; 594 antecedents were identified. Analysis identified 508 unique antecedents, 28 grouped antecedents, 5 factors and 3 clusters.

A Comparison of Antecedents of Different Types of Innovation – V - Glor, Eleanor D (Innovation Journal, 2021)
Antecedents of innovation precede their implementation and probably influence which innovations and whether they are approved and implemented. Antecedents have been identified in a considerable number of types of innovation. Are they the same in these types? A systematic literature review (SLR) of antecedents of policy innovation found 594 antecedents, 508 of them unique, in 87 articles on trailblazing and adoption. So many antecedents suggest a lack of clarity about what the antecedents of policy innovation may be. They have been clarified for policy innovation. In this paper the antecedents of policy innovation are compared to antecedents of private, public sector and social innovation identified in literature reviews, SLRs and metaanalyses to see whether common or different antecedents are identified in these literatures. While the literature often implies antecedents of different types of innovation are the same by lumping them together, they were found to vary somewhat by type of innovation, especially trailblazing and higher-level factors and clusters. External antecedents were only found to be important for policy innovation and dissemination; political antecedents were particularly important for trailblazing; internal antecedents were important for all types of innovation. Literature on antecedents of private innovations did not consider external or political antecedents. Four research questions are addressed: Q. 1: At what level should antecedents of innovation be analyzed and compared? Q. 2: How do antecedents identified for different types of innovation compare—private, public and public-social sectors? Q. 3: How do clusters identified for different types of public sector innovation compare— processes; trailblazing and adoption of policy; dissemination; private, public, public-social sectors? Q. 4: Do a common set of unique and grouped antecedents, factors and clusters influence all types of innovation equally or are their antecedents discernably different? Key words: antecedents of innovation, comparison of antecedents, types of innovation, systematic literature review.

Factors (Antecedents) Influencing Creation and Fate of Innovations and their Organizations – III - Glor, Eleanor D (Innovation Journal, 2021)
Despite recommendations for more quantitative analyses of public sector innovation factors (Glor, 2014a; de Vries, Bekker and Tummers, 2016), there has been limited examination of them. This paper identifies and explores six factors (ideology, politics, the economy, external support, resources, effects) that influenced the introduction and survival or termination of the first time these public sector innovations and their five organizations (I&O) were introduced in North America. It assesses their key antecedent factors before creation (Time 1) and the same factors again at the time of their fate 15 to 44 years later (Time 2). They were assessed with a new measurement instrument examining the six factors (Glor, 2017a). The tool has 1267 statements (items) and 555 pairs of data, with scoring distributed on a five-point Likert scale. Three expert raters completed the instrument (Glor, 2017b). Based on mean scores, the most important factors in Time 1 (creation of I&O) were found to be the economy, resources, effects and external support and in Time 2 (survival/termination) ideology and politics. This methodology could potentially be used to study the remaining 154 Government of Saskatchewan (GoS) population’s innovations and that of other populations.

Analysis of Antecedents of Trailblazing and Adoption of Public Policy Innovation Identified by a Systematic Literature Review - II - Glor, Eleanor D (2021)
The paper organizes and summarizes the conditions (antecedents) researchers and practitioners identified as occurring prior to trailblazing and adoption of public policy (including program) innovation, as identified in a systematic literature review. The review identified 87 relevant documents and 594 antecedents. Trailblazing of innovation is Rogers’ (1995) first two stages of adoption—innovation (invention) and early adoption (identified here as second and third adoptions in a government’s community or population). The antecedents are analyzed into grouped antecedents, factors and clusters. The most-mentioned grouped antecedents were citizen pressure, process, structure and political culture. The most-mentioned factors were innovation drivers, people, policy/process, and context. The factors were organized into clusters—external, political and internal. Based on number of mentions the literature considered the internal cluster the most important. The most-mentioned factors in external cluster were context and people; in political cluster, drivers, political context and political actors; in internal cluster, innovation process, drivers, people and internal environment. Multiples more antecedents were identified for internal cluster than the others. Lack of consistent definitions and the mixing of stages and levels in the literature has hampered understanding of antecedents and placed limitations on this study. The literature sometimes distinguished external and internal cluster; the current analysis also considers a political cluster, which is especially important to trailblazing of public policy innovations.

Conclusion: Important Antecedents of Public Policy Innovation as Revealed in a Systematic Literature Review – VI - Glor, Eleanor D (Innovation Journal, 2021)
A systematic literature review (SLR) of antecedents of trailblazing and adoption of public policy innovation was conducted. Many antecedents were found—594. A terminology and classification system for them was therefore developed (unique antecedents-508, grouped antecedents-28, factors-15, clusters-3). Differences among trailblazing/adoption and quantitative/qualitative studies were explored six ways. Eleven grouped antecedents of trailblazing were importantly different from those of adoption, 17 were not. Grouped antecedents of quantitative and qualitative studies were not importantly different and so were used as the standard. Only trailblazing had different antecedents from the other three types of study (adoption, quantitative, qualitative). Eight grouped antecedents were the best indicators of policy innovation. Of the three clusters of antecedents, external and internal cluster grouped antecedents were equally important for all four kinds of study; political cluster antecedents were different for trailblazing. Although there was no one best political indicator (large difference from adoption) for trailblazing, political cluster was more important for trailblazing than adoption. Political cluster was higher (had a higher proportion of mentions) and internal cluster lower for trailblazing; political cluster was lower and internal cluster higher for adoption. The important antecedents for public policy innovation were compared to those for the private/public sector, public process/policy and public/social innovation: Differences were found. The best antecedent indicators of trailblazing of policy innovation identified in the literature were external environment, drivers, obstacles (external) and people (internal).